Cognitive function, depressive symptoms and syphilis in HIV-positive and HIV-negative individuals. (April 2019) - De Francesco, Davide; Winston, Alan; Underwood, Jonathan; Cresswell, Fiona V; Anderson, Jane; Post, Frank A; Williams, Ian; Mallon, Patrick WG; Sachikonye, Memory; Babalis, Daphne; Vera, Jaime H; Bagkeris, Emmanouil; et al.
We evaluated associations between history of syphilis infection and both cognitive function and depressive symptoms in people living with HIV (PLHIV) and comparable HIV-negative controls. Syphilis serological tests, cognitive function and depression were assessed in PLHIV and controls participating in the Pharmacokinetic and Clinical Observations in People Over Fifty study. Cognitive test scores were converted to demographically adjusted T-scores (mean = 50, SD = 10) and then averaged to obtain a global T-score. Severity of depressive symptoms was assessed via the Patient Health Questionnaire-9. Associations of syphilis with global T-scores and depression were assessed using median regression. The 623 PLHIV and 246 HIV-negative controls were predominantly male (89.3% and 66.5%) with median age (interquartile range [IQR]) of 57 (53–63) and 58 (53–63) years, respectively. PLHIV had lower global cognitive T-scores (median [IQR] 48.7 [45.1, 52.1] versus 50.5 [47.0, 53.9], p < 0.001), more severe depressive symptoms (median [IQR] 4 [1, 10] versus 1 [0, 3], p < 0.001) and were more likely to report history of syphilis infection (22.0% versus 8.1%) than controls. There was no significant association between history of syphilis and global cognitive function in either PLHIV (p = 0.69) or controls (p = 0.10). Participants with a history of syphilis had more severe depressive symptoms (median [IQR] 4 [1, 9] versus 2 [0, 8], p = 0.03); however, the association became non-significant (p = 0.62) after adjusting for HIV status and potential confounders. Despite the higher prevalence of syphilis infection in PLHIV, there was no evidence of an association between history of syphilis infection and impaired cognitive function nor depressive symptoms after accounting for potential confounders.